Histopathological Changes in Animal Models by Catheters Coated with Saudi Medicinal Herb Evolvulus alsinoides L. Extract in Urinary Tract Infections by Klebsiella pneumoniae - Mohideen, Abubucker Peer; Alsharif, Mohammed H. Karrar; Poyil, Muhammad Musthafa (Indian Journal of Pharmaceutical Education and Research, 2024)
Background: Catheter-Associated Urinary Tract Infections (CA-UTIs) pose a significant danger especially when they are caused by multi-drug resistant strains of Klebsiella pneumoniae. As elsewhere in the world, Saudi Arabia also shows a higher prevalence of Klebsiella pneumoniae which complicates the treatment and management of the CA-UTIs. To tackle this, it is urgent to develop novel antibacterial compounds from natural sources and, phytochemicals have always been potential candidates. Evolvulus alsinoides is a traditional medicinal plant found in Saudi Arabia possesses proven activities against CA-UTI causing bacteria including Klebsiella pneumoniae. Aim: The present study was aimed to investigate the antibacterial, antiinflammatory and anti-biofilm activities of Evolvulus alsinoides plant extract against multidrug resistant Klebsiella pneumoniae. Materials and Methods: The study was designed to coat the methanolic extract of Evolvulus alsinoides on catheters and evaluate its efficacy on Guinea pigs (Cavia porcellus). Inflammatory marker concentrations, SOD (reactive oxygen species), and the MPO (neutrophil recruitment) were also evaluated to understand the effect of this plant extract on tissue damage. Results: Evolvulus alsinoides displayed the presence of alkaloids, flavonoids, phenols, saponins, tannins and fixed oils. Klebsiella pneumoniae was resistant to four of the five antibiotics tested. The extract showed anti-Klebsiella pneumoniae activity and the MIC was 4.61 mg/mL. Showing its anti-biofilm activity, 31.23 μg/mL of the extract reduced the catheter biofilm to 16.23%±2.4. At 5 μg/mg, the extract displayed anti-inflammatory markers as MPO degranulation 49.36%±1.4, MDA 0.142±0.001 nmol/mg protein and SOD 58.97±1.6 units/mL. Conclusion: In the light of these findings, it could be assessed that the Evolvulus alsinoides extract possesses antibacterial, anti-biofilm and anti-inflammatory activities, and the extract should further be studied to develop it for its clinical usage.
Keywords: Biofilms; CA-UTIs; Guinea pigs; Inflammatory markers; Klebsiella pneumoniae; MDR; strains; Urinary catheters; Evolvulus alsinoides